A Conditional Process Model to Explain Somatization During Coronavirus Disease 2019 Epidemic: The Interaction Among Resilience, Perceived Stress, and Sex - Shangguan, Fangfang; Zhou, Chenhao; Qian, Wei; Zhang, Chen; Liu, Zhengkui; Zhang, Xiang Yang (Frontiers in Psychology, 2021)
Background: More than 15% of Chinese respondents reported somatic symptoms in the last week of January, 2020. Promoting resilience is a possible target in crisis intervention which can alleviate somatization. Objectives: This study aims to investigate the relationship between resilience and somatization, as well as the underlying possible mediating and moderating mechanism, in a large sample of Chinese participants receiving a crisis intervention during COVID-19 epidemic, Methods: Participants were invited online to complete demographic information and questionnaires. The Symptom Checklist-90 somatization subscale, 10-item Connor-Davidson resilience scale, and 10-item Perceived Stress Scale were measured. Results: A total of 2557 participants were included. Spearman correlation analysis revealed that lower resilience was associated with more somatic symptoms (p < 0.001). The conditional process model was proved (Indirect effect = −0.01, 95% CI = [−0.015, −0.002]). The interaction effects between perceived stress and gender predicted somatization (b = 0.05, p = 0.006). Conclusions: Resilience is a key predictor of somatization. The mediating effects of perceived stress between resilience and somatization work in the context of gender difference. Gender-specific intervention by enhancing resilience is of implication for alleviating somatization during the COVID-19 epidemic.